A promoção de discriminação simples, sem erro, de letras e suas inversões: seus efeitos em testes de matching de identidade e arbitrário - Matos, Daniel Carvalho de (2007)
The present research had two goals: (a) to test the efficacy of a delayed prompt procedure to develop errorless discrimination between letters and their rotations, and (b) to test the effects of the discrimination training when MTS trials with the trained letters, theirs rotations, and similar letters were presented. Participated in the study 9 children (aged 3 to 6) who did not have a perfect performance when discrimination between pairs of graphically similar letters and their rotations (b, d, n, u, p, q, and their 270o rotations, and the letter B, D, N, U, P, Q and their 180o rotations). A test with identity-matching-to-sample trials involving the S+ letters as sample stimuli and the same letters, their rotations and similar letters as comparison stimuli was first conducted. A discrimination training of each testes letter (S+) and its rotation (S_) was then conducted: During training, colors (previously established as S+ and S-) were superimposed on the new S+ (letter) and S- (letter-rotation) with longer delays after each successful trial, until the child systematically responded choosing S+ before the color was presented. After training the initial identity MTS test was replicated, followed by a test of arbitrary MTS: trials involving letters and colors were presented, to test the emergency of conditional discrimination. Results suggested that 4 children developed conditional discriminations indicating the emergency of arbitrary stimulus classes. Results also indicated that although the discrimination training was effective in producing simple discrimination, it was not sufficient to guarantee good performance when identity-matching-to-sample trials were presented